Aktivitas Enzim Amilase Isolat Bakteri Amilolitik dari Tepung Sagu Basah dan Lingkungan Tempat Penyediaannya Secara Tradisional di Jayapura - Suprapto Surapto; Tri Gunaedi; Basa T. Rumahorbo (Jurusan Biologi FMIPA Universitas Cenderawasih, 2014)
The study about the activity of the enzyme amylase from amylolytic bacterial isolates from wet sagoo starch and its traditional provision environment had been done in Jayapura. The purposes of this study were to determine the activity of amylase enzyme and to identify the bacteria isolated from wet sagoo starch and its processing environment in Jayapura district. The method used was an experimental laboratorium in which isolation of amylolytic bacteria was performed by using nutrient agar medium with 1% soluble starch on spreed pour plate method. The enzyme activity was detected with 0.2% iodine in 2% potassium iodide which were able to form a clear zone. The protein content of the crude enzyme extract was determined by the Bradford method using bovine serum albumin (BSA). Amylase enzyme activity was determined by the formula: DUN/ml = [(R0-R1)/R0] [dilution factor] DUN/ml (dextrinizing units per ml). The results showed that there were 15 isolates amylolytic bacteria. Four (4) bacterial isolates have amylolytic power of more than 30 mm. The amilase activity of amylolytic bacterial of all isolates were quite high: which were 35 577, 18 903, 32 106 and 46 600 U/mg for SU4, SU13, SU23 and SU40 respectively. The identification of isolates indicated that the three isolates are members of the Bacillus cereus ATCC 14 579 types with a similarity value of 71.70% to 81.10%, and one isolate is Bacillus subtilis ATCC 6501 members with a similarity value of 94.30%. Keywords: Amylolytic bacteria, amylase activity, characterization, sago flour.